536 Conservative Management of the Colonic Gallstone. (19th August 2022) - Hurst, K; Peiris, B; Booth, M
Abstract: A 74-year-old woman presents with a 7-day history of increasing lower abdominal pains and reduced bowel movements; resulting in absolute constipation.Twenty-four hours prior to admission she also had symptoms of nauseous and significant abdominal distention. Her past medical history included; diverticulitis, type 2 diabetes, hypercholesterolemia, an ultrasound scan in 2005 confirming gallstones, but no previous abdominal surgery.She was initially treated for bowel obstruction and a CT arranged. CT showed a 4.5 cm gallstone in mid-sigmoid colon and a cholecystocolonic fistula. She was booked for colonoscopy±laparotomy, but on the morning of her planned procedure she repeatedly opened her bowels. Subsequent colonoscopy was negative and repeat CT confirmed the stone was no longer within the gastrointestinal tract. Several case reports have clearly documented the presence of a cholocystocholic fistula leading to sigmorectal bowel obstruction from gallstones. These reports, however, have all implied that management should primarily be with a laparotomy. Although colonoscopy has also been trialled, few cases appear to have been successful and conversion to laparotomy has been high. This case report highlights a role for conservative management in colonic gallstones, avoiding the morbidity and mortality associated with laparotomy +/- bowel resection.